Q: Identify the type of error in the sentence. If the sentence contains no error, select correct. Jane was not only beautiful but was known as a humble person.
a. definition structure b. explanation

structure c. parallel structure d. dangling construction e. correct

A: Jane was not only beautiful be was known as a humble person. The error is parallel structure.

Expert answered|Saul1|Points 10|

Question|Rated bad

Asked 7/11/2012 7:41:02 AM

Updated 9/4/2014 5:59:36 AM

1 Answer/Comment

This conversation has been flagged as incorrect.

Flagged by debnjerry [9/4/2014 5:59:36 AM]

Rating

3

Jane was not only beautiful be was known as a humble person. The error is parallel structure.

Added 9/4/2014 5:59:35 AM

This answer has been confirmed as correct, not copied, and helpful.

Identify the type of error in the sentence. If the sentence contains no error, select correct. By calling every hour, my mother received Jamie's call.
a. definition structure b. explanation structure c. parallel structure d. dangling construction e. correct
**Weegy:** C is your answer **User:**
Identify the type of error in the sentence. If the sentence contains no error, select correct. To enter college, an admission exam must be passed.
a. definition structure b. explanation structure c. parallel structure d. dangling construction e. correct
**Weegy:** c. parallel structure d. dangling construction (More)

Question

Expert Answered

Updated 9/4/2014 5:58:42 AM

2 Answers/Comments

By calling every hour, my mother received Jamie's call. The error is dangling construction.

Added 9/4/2014 5:58:02 AM

This answer has been confirmed as correct, not copied, and helpful.

To enter college, an admission exam must be passed. The error is dangling construction.

Added 9/4/2014 5:58:29 AM

This answer has been confirmed as correct, not copied, and helpful.

Each and every are indefinite pronouns.
**Weegy:** Can i help further? (More)

Question

Expert Answered

Updated 9/4/2014 4:54:37 AM

1 Answer/Comment

9(x - 6) = 8(x + 6)
**Weegy:** 9/6=x/8
8*(9/6)=x
12=x (More)

Question

Expert Answered

Updated 7/17/2012 9:38:02 AM

1 Answer/Comment

3(x - 2) + 4(2x - 6) = 6(x - 4) + 8(2x + 1)
**Weegy:** Simplifying
3(x + -2) + 4(2x + -6) = 6(x + -4) + 8(2x + 1)
Reorder the terms:
3(-2 + x) + 4(2x + -6) = 6(x + -4) + 8(2x + 1)
(-2 * 3 + x * 3) + 4(2x + -6) = 6(x + -4) + 8(2x + 1)
(-6 + 3x) + 4(2x + -6) = 6(x + -4) + 8(2x + 1)
Reorder the terms:
-6 [ + 3x + 4(-6 + 2x) = 6(x + -4) + 8(2x + 1)
-6 + 3x + (-6 * 4 + 2x * 4) = 6(x + -4) + 8(2x + 1)
-6 + 3x + (-24 + 8x) = 6(x + -4) + 8(2x + 1)
Reorder the terms:
-6 + -24 + 3x + 8x = 6(x + -4) + 8(2x + 1)
Combine like terms: -6 + -24 = -30
-30 + 3x + 8x = 6(x + -4) + 8(2x + 1)
Combine like terms: 3x + 8x = 11x
-30 + 11x = 6(x + -4) + 8(2x + 1)
Reorder the terms:
-30 + 11x = 6(-4 + x) + 8(2x + 1)
-30 + 11x = (-4 * 6 + x * 6) + 8(2x + 1)
-30 + 11x = (-24 + 6x) + 8(2x + 1)
Reorder the terms:
-30 + 11x = -24 + 6x + 8(1 + 2x)
-30 + 11x = -24 + 6x + (1 * 8 + 2x * 8)
-30 + 11x = -24 + 6x + (8 + 16x)
Reorder the terms:
-30 + 11x = -24 + 8 + 6x + 16x
Combine like terms: -24 + 8 = -16
-30 + 11x = -16 + 6x + 16x
Combine like terms: 6x + 16x = 22x
-30 + 11x = -16 + 22x
Solving
-30 + 11x = -16 + 22x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-22x' to each side of the equation.
-30 + 11x + -22x = -16 + 22x + -22x
Combine like terms: 11x + -22x = -11x
-30 + -11x = -16 + 22x + -22x
Combine like terms: 22x + -22x = 0
-30 + -11x = -16 + 0
-30 + -11x = -16
Add '30' to each side of the equation.
-30 + 30 + -11x = -16 + 30
Combine like terms: -30 + 30 = 0
0 + -11x = -16 + 30
-11x = -16 + 30
Combine like terms: -16 + 30 = 14
-11x = 14
Divide each side by '-11'.
x = -1.272727273
Simplifying
x = -1.272727273 ] **User:** 3(x + 2) = 6
**Weegy:** Simplifying
3(x + 2) = 6
Reorder the terms:
3(2 + x) = 6
(2 * 3 + x * 3) = 6
(6 + 3x) = 6
Add '-6' to each side of the equation.
6 + -6 + 3x = 6 + -6
Combine like terms: 6 + -6 = 0
0 + 3x = 6 + -6
3x = 6 + -6
Combine like terms: 6 + -6 = 0
3x = [ 0
Solving
3x = 0
Solving for variable 'x'.
Move all terms containing x ... (More)

Question

Expert Answered

Updated 6/4/2014 12:56:51 AM

2 Answers/Comments

3(x - 2) + 4(2x - 6) = 6(x - 4) + 8(2x + 1)
**Weegy:** x = -14/11 (More)

Question

Expert Answered

Updated 7/3/2014 2:17:17 PM

1 Answer/Comment

27,403,141 questions answered

There are no comments.